The effects of different ph and salinities on growth rate and carrageenan yield of gracilaria manilaensis - Mohamad Hidayat, Nor Salamah; Mohammad Noor, Normawaty; Darnis, Deny Susanti; Saad, Shahbudin; Mukai, Yukinori (Universiti Teknologi Malaysia, 2015)
The high demand of seaweed for their polysaccharide namely carrageenan leads to the commercial production of carrageenophytes through mariculture. Based on literatures it is well documented that growth rate and carrageenan yield depend on environmental factors such as salinity, pH, temperatures, light intensity and water movement. In this study, growth rate and carrageenan yield of Gracilaria manilaensis, a red seaweed, was determined at different pH and salinities. G. manilaensis was cultured under laboratory conditions in a 500 mL flask at different salinities (15 psu, 20 psu and 25 psu ) and pH (7.6, 7.8, and 8.0) for 21 days. At the end of experiment, the growth rate was determined followed by carrageenan analysis. From the analysis, growth rate was highest at salinity of 15 psu and pH 7.6 with 1.3 ± 0.2 % day-1.For carrageenan analysis, the seaweed was air dried for about a week until it reached a constant weight. Farmed G. manilaensis was used as control and carrageenan yield was determined from farmed G. manilaensis. It gives yield of 50.2 ± 10.9 %. For carrageenan yield analysis, the highest value was demonstrated at salinity of 25 psu and pH 8.0 with 91.7± 14.4 %. Result shows that carrageenan yields from G. manilaensis under laboratory conditions are higher compared to farmed Gracillaria. This indicates that the quality of G. manilaensis in term of carrageenan content can be optimized under certain growth conditions. This is important as this species has the potential to be commercialized for pharmaceutical and food industries.